Dancing with manatees - McNulty, Faith; Shiffman, Lena (New York : Scholastic Inc., 1994)
Examines the physical characteristics, behavior, and evolution of this gentle creature.
"Grade 2 & 3."--Cover.
Keywords: Manatees -- Juvenile literature; Manatees; Manatees